Socio-economic Assessment of the Sustainable Development Interventions of the Island of Ikaria, Based on the Utilization of its Cultural and Environmental Reserve (CER), in the Context of the Circular Economy - Verrou, Athina; Vythoulka, Anastasia; Mikrou, Ioanna; Dimas, Petros; Stamopoulos, Dimitrios; Barlas, Charalampos; Tsakanikas, Aggelos; Moropoulou, Antonia (Technical Annals, 2025)
The purpose of this study is the socio-economic assessment of the Sustainable Development interventions of Ikaria Island, based on the exploitation of its Cultural and Environmental Reserve (CER), focusing on how these interventions affect GDP and employment, both at regional and national level. The interventions studied include projects related to road infrastructure and the CER of the island. An input-output analysis was used to assess the socio-economic impact of the interventions. Based on the results of the input-output analysis, the implementation of the sustainable development proposals on Ikaria Island will result in a change in GDP of €41.15 million at the level of the national economy and €20.57 million at the level of the North Aegean region economy. In terms of employment, the implementation of the sustainable development proposals will result in the creation of 1052 jobs at national level and 594 jobs in the North Aegean region. In conclusion, the sustainable development interventions will have a positive social and economic impact on the island of Ikaria.